Intelligent classification of palm oil tree pollination using E-nose - Abdul Rahim, Jalil; Muhammad Sharfi, Najib; Suhaimi, Mohd Daud; Mujahid, Mohamad; Saiful Nizam, Tajuddin; Che Mohd Aizal, Che Mohd; Razam, Abd Latip; Mohammad Saiful Nizam, Ismail; Mohamad Nor Azizi, Shabudin; Wan Rusyidah, W. Rusik (Penerbit UMP, 2020)
The pollination period is one of the crucial steps needed to ensure crop yield increases, especially in palm oil palm plantations. Most of the research has difficulty determining the pollination period of palm oil. Many problems contribute to this problem, such as difficut to reach and depedency of the polination insect as the insect activity is influenced by the surrounding enviroment.E-Nose can help determine the period by classifiy odour pattern of the male and female palm oil flower. The pattern of each of the flowers were classified using cased – based reasoning artificial intelligent technique. This paper shows the research of the palm oil pollination flower odour profile pattern using case-based reasoning (CBR) classifier.